PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA SHARED SERVICES DEPARTEMENT HEAD DI PT. ANGKASA PURA I (PERSERO) KANTOR CABANG BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - AKBAR GUMIWANG, SATRIA (Jurnal Ilmu Manajemen (JIM), 2016)
The role of organizational culture in the airport affairs services corporate was important. Servants and employees have an obligation into their job with apply the corporate culture sustainably. Based on this matter, the servants and the employee are demanded to implement corporate culture. One of the factors that could influence the implementation of organizational culture was job satisfaction. The servants and employees who felt satisfied on the job, then they will decide committed to the company. With the existence of organizational commitment, the servants and employees were more responsible in every task on their job, so that job satisfaction will incresingly raises. The purpose of this research was to analyze the effect of organizational culture on job satisfaction. And the role of organizational commitment as an mediating variable on the effect organizational culture on job satisfaction. Samples from this research were the servants and employees in shared services departement head, amounting to 32 people. The data analysis technique used is the analysis of the alternative method of Structural Equation of Partial Least Square which is supported by software version 2.0. The results of the research explained that organizational culture positive and significant effect on job satisfaction. Organizational Culture positive and significant effect on organizational commitment. Organizational commitment positive and significant effect on job satisfaction. Organizational commitment mediates the effect of organizational culture on job satisfaction. Keywords: organizational culture, organizational commitment, job satisfaction.